An Ill Wind? Climate Change, Migration, and Health - McMichael, Celia (National Institute of Environmental Health Sciences, 2012)
Background: Climate change is projected to cause substantial increases in population movement in coming decades. Previous research has considered the likely causal influences and magnitude of such movements and the risks to national and international security. There has been little research on the consequences of climate-related migration and the health of people who move. Objectives: In this review, we explore the role that health impacts of climate change may play in population movements and then examine the health implications of three types of movements likely to be induced by climate change: forcible displacement by climate impacts, resettlement schemes, and migration as an adaptive response. Methods: This risk assessment draws on research into the health of refugees, migrants, and people in resettlement schemes as analogs of the likely health consequences of climate-related migration. Some account is taken of the possible modulation of those health risks by climate change. Discussion: Climate-change–related migration is likely to result in adverse health outcomes, both for displaced and for host populations, particularly in situations of forced migration. However, where migration and other mobility are used as adaptive strategies, health risks are likely to be minimized, and in some cases there will be health gains. Conclusions: Purposeful and timely policy interventions can facilitate the mobility of people, enhance well-being, and maximize social and economic development in both places of origin and places of destination. Nevertheless, the anticipated occurrence of substantial relocation of groups and communities will underscore the fundamental seriousness of human-induced climate change.